Dampak Pengelolaan Kelas Berdasarkan Gender Terhadap Motivasi Belajar Siswa di SMPIT Ad-Dhurroh - Ramdhani, Putri Suci; Munawwarah, Tarisa; Kholiza, Nur Alfiana; Siregar, Nur Khofifah; Nasution, Abdul Fattah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the impact of classroom management based on gender on student learning motivation at Ad-Dhurroh IT Middle School. Using descriptive quantitative methods, this research involved 46 students taken as samples from a total population of 460 students. Data collection techniques were carried out through questionnaires and documentation studies, with data analysis using simple correlation. The research results show that classroom management based on gender has a positive contribution to student learning motivation, with a t value of 4.530 (greater than t table 2.907) and a significance of 0.083 (greater than 0.05). The coefficient of determination (R²) value of 0.067 indicates that classroom management contributes 6.7% to student learning motivation. Most students were in the medium motivation category (61%), followed by the low category (26%), and the high category (13%). This research concludes that classroom management based on gender influences students' learning motivation and provides recommendations for developing more innovative classroom management methods.